Charity and favoritism in the field: Are female economists nicer (to each other)? - Jason Abrevaya; Daniel S. Hamermesh (Institute for the Study of Labor (IZA), 2010)
Using a very large sample of matched author-referee pairs, we examine how the gender of referees and authors affects the former's recommendations. Relying on changing matches of authors and referees, we find no evidence of gender differences among referees in charitableness toward authors; nor do we find any effect of the interaction between the referees' and authors' gender. With substantial research showing gender differences in fairness, the results suggest that an ethos of objectivity can overcome tendencies toward same-group favoritism/opposite-group discrimination.
Keywords: J71; 330; Discrimination; gender; academe; Wirtschaftswissenschaftler; Akademische Berufe; Soziale Beziehungen; Patronage; Geschlechterdiskriminierung; Schätzung; USA